Regional Emergence of Candida auris in Chicago and Lessons Learned From Intensive Follow-up at 1 Ventilator-Capable Skilled Nursing Facility. (14th April 2020) - Pacilli, Massimo; Kerins, Janna L; Clegg, Whitney J; Walblay, Kelly A; Adil, Hira; Kemble, Sarah K; Xydis, Shannon; McPherson, Tristan D; Lin, Michael Y; Hayden, Mary K; Froilan, Mary Carl; Soda, Elizabeth; et al.
Abstract: Background: Since the identification of the first 2 Candida auris cases in Chicago, Illinois, in 2016, ongoing spread has been documented in the Chicago area. We describe C. auris emergence in high-acuity, long-term healthcare facilities and present a case study of public health response to C. auris and carbapenemase-producing organisms (CPOs) at one ventilator-capable skilled nursing facility (vSNF-A). Methods: We performed point prevalence surveys (PPSs) to identify patients colonized with C. auris and infection-control (IC) assessments and provided ongoing support for IC improvements in Illinois acute- and long-term care facilities during August 2016–December 2018. During 2018, we initiated a focused effort at vSNF-A and conducted 7 C. auris PPSs; during 4 PPSs, we also performed CPO screening and environmental sampling. Results: During August 2016–December 2018 in Illinois, 490 individuals were found to be colonized or infected with C. auris . PPSs identified the highest prevalence of C. auris colonization in vSNF settings (prevalence, 23–71%). IC assessments in multiple vSNFs identified common challenges in core IC practices. Repeat PPSs at vSNF-A in 2018 identified increasing C. auris prevalence from 43% to 71%. Most residents screened during multiple PPSs remained persistently colonized with C. auris . Among 191 environmental samples collected, 39% were positive for C. auris, including samples from bedrails, windowsills, and shared patient-care items. Conclusions: High burden in vSNFs along with persistent colonization of residents and environmental contamination point to the need for prioritizing IC interventions to control the spread of C. auris and CPOs. Abstract : This report describes Candida auris emergence in Chicago during August 2016–December 2018, and public health response at one ventilator-capable skilled nursing facility with high colonization burden. Improved adherence to infection control and environmental disinfection is needed to control spread.